1996
DOI: 10.1104/pp.110.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Branching in Pea (Action of Genes Rms3 and Rms4)

Abstract: The nonallelic ramosus mutations rms3-2 and rms4 of pea (Pisum safivum 1.) cause extensive release of vegetative axillary buds and lateral growth in comparison with wild-type (cv Torsdag) plants, i n which axillary buds are not normally released under the conditions utilized. Crafting studies showed that the expression of the rms4 mutation i n the shoot is independent of the genotype of the rootstock. I n contrast, the length of the branches at certain nodes of rms3-2 plants was reduced by grafting to wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
143
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 19 publications
9
143
3
Order By: Relevance
“…Some studies have demonstrated that in the strigolactone mutants the auxin levels were higher (Beveridge et al 1997b;Bennett et al 2006) whereas others that the mutants and the wild type did not differ (Beveridge et al 1996;Morris et al 2001;Arite et al 2009). There is also support for a role of strigolactones in reducing polar auxin transport both by means of radiolabeled auxins and PIN efflux marker lines, although contradictory results concerning subcellular relocalisation of PINs in root tips have been reported in different experiments and when the root and shoot systems were compared (Beveridge et al 2000;Bennett et al 2006;Lazar and Goodman 2006;Lin et al 2009;Crawford et al 2010;Shinohara et al 2013).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated that in the strigolactone mutants the auxin levels were higher (Beveridge et al 1997b;Bennett et al 2006) whereas others that the mutants and the wild type did not differ (Beveridge et al 1996;Morris et al 2001;Arite et al 2009). There is also support for a role of strigolactones in reducing polar auxin transport both by means of radiolabeled auxins and PIN efflux marker lines, although contradictory results concerning subcellular relocalisation of PINs in root tips have been reported in different experiments and when the root and shoot systems were compared (Beveridge et al 2000;Bennett et al 2006;Lazar and Goodman 2006;Lin et al 2009;Crawford et al 2010;Shinohara et al 2013).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
“…Auxin is also regulated by positive feedback loops between biosynthesis and transport, so the higher levels of auxin biosynthesis may cause the higher levels of transporter proteins observed in primary roots (Ruyter-Spira et al 2011) and also the higher levels of auxin measured at the bases of cuttings from tomato strigolactone mutants . Opposing evidence for this theory is that the strigolactone mutants of pea do not necessarily have a higher auxin content than that of the wild type (Beveridge et al 1996;Morris et al 2001). Additional proof against strigolactone directly regulating auxin biosynthesis is found in root hair lengths, where exogenous treatments with auxins using the PIN efflux pathway were unable to restore the phenotype (Koltai et al 2010), suggesting a more direct interaction with the PIN pathway.…”
Section: Are All Strigolactone Effects Related To Auxin?mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, many branching mutants have been isolated that have problems with auxin, cytokinin, or brassinosteroids, for example, and show highly pleiotropic phenotypes typical for these hormones (Lincoln et al, 1990;Azpiroz et al, 1998;Tantikanjana et al, 2001). However, a class of mutants were isolated that displayed a specific increase in bud outgrowth that was not correlated with any known hormonal signal (Beveridge et al, 1996(Beveridge et al, , 1997. Paradoxically, the mutants were found to have generally higher levels of auxin and lower levels of xylem cytokinin, facts difficult to reconcile with ideas about the roles of auxin and cytokinin in regulating bud outgrowth (Beveridge et al, 1997).…”
mentioning
confidence: 99%
“…Mutant phenotypes were rescued by grafting with wild-type tissue, even in interstock grafts where small pieces of wild-type stem tissue were grafted between mutant rootstock and shoot tissue (Napoli, 1996;Foo et al, 2001). Other mutants were not rescued by grafting but were instead suggested to lack response to SMS (Beveridge et al, 1996;Booker et al, 2005). Grafting studies also showed that outgrowth induced by decapitation in SMS mutant plants cannot be inhibited by IAA applied to the stump unless a wild-type rootstock is present .…”
mentioning
confidence: 99%